PEMBELAJARAN BERDIFERENSIASI DALAM MENULIS TEKS PUISI SISWA KELAS X FASE E SMA NEGERI 5 PADANG - Thassya Ferdilla Putri; Lira Hayu Afdetis Mana; Indriani Nisja (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the effectiveness of implementing differentiated learning in writing poetry texts for tenth-grade students at SMA Negeri 5 Padang. The background of this study is based on students' low poetry writing skills, which tend to be monotonous and unable to express ideas creatively. The research method used was a qualitative approach with a descriptive research type. The subjects were tenth-grade students selected purposively, while data collection techniques included observation, interviews, writing tests, and documentation. Data were analyzed using data reduction, data presentation, and conclusion drawing techniques. The results showed that the implementation of differentiated learning was able to improve students' poetry writing skills as seen from aspects of accurate diction, figures of speech, imagination, and theme suitability. Students became more creative, bold in expressing feelings, and were able to develop a variety of language styles. Thus, differentiated learning has proven effective in improving the quality of students' poetry writing texts.